How to Help the Poor to Save a Bit: Evidence from a Field Experiment in Kenya - Merve Akbas; Dan Ariely; David A. Robalino; Michael Weber (Institute for the Study of Labor (IZA), 2016)
Worldwide, the majority of workers hold jobs in the informal sector that do not provide access to social insurance programs. We partnered with a savings product provider in Kenya to test the extent to which behavioral interventions and financial incentives can increase the saving rate through a voluntary pension program for informal workers with low and irregular income. Our experiment lasted for six months and included a total of twelve conditions. The control condition received weekly reminders and balance reporting via text messages. The treatment conditions received in addition one of the following interventions: (1) reminder text messages framed as if they came from the participant's kid (2) a golden colored coin with numbers for each week of the trial, on which participants were asked to keep track of their weekly deposits (3) a match of weekly savings: The match was either 10% or 20% up to a certain amount per week. The match was either deposited at the end of each week or the highest possible match was deposited at the start of each week and was adjusted at the end. Among these interventions, by far the most effective was the coin: Those in the coin condition saved on average the highest amount and more than twice as those in the control condition. We hypothesize that being a tangible track-keeping object; the coin made subjects remember to save more often. Our results support the line of literature suggesting that saving decisions involve psychological aspects and that policy makers and product designers should take these influences into account.
Keywords: G21; B49; D03; 330; behavioral economics; field experiment; savings